2021
DOI: 10.1002/14651858.cd013792.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Progestogens for preventing miscarriage: a network meta-analysis

Abstract: Analysis 2.3. Comparison 2: Threatened miscarriage: Dydrogesterone versus placebo, Outcome 3: Preterm birth (defined as birth before 37 weeks of gestation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 89 publications
0
40
0
5
Order By: Relevance
“…Supplementation with different progestogens in early pregnancy has been attempted to rescue a pregnancy in women with early pregnancy bleeding to treat threatened miscarriage [ 26 ]. Oral dydrogesterone are used to treat threatened abortion which was further stated effective in recent study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with different progestogens in early pregnancy has been attempted to rescue a pregnancy in women with early pregnancy bleeding to treat threatened miscarriage [ 26 ]. Oral dydrogesterone are used to treat threatened abortion which was further stated effective in recent study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there have been conflicting reports on the effectiveness of progesterone in the treatment of TM. A recent Cochrane review concluded that the available evidence suggests that progestogens probably make little or no difference in the live birth rate in women with TM [27].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the combined data from the PROMISE and PRISM trials in women with RM, vaginal progesterone therapy may be offered up until the 16th week of gestation if bleeding due to impending miscarriage is diagnosed 126 . Based on data from the recent Cochrane meta-analysis, this recommendation can be expanded to include women with bleeding due to impending miscarriage and one or two prior spontaneous miscarriages 124 .…”
Section: Guidelinementioning
confidence: 99%
“…SSW angeboten werden, wenn eine Abortus-imminens-Blutung diagnostiziert wird 126 . Basierend auf den Daten der aktuellen Cochrane-Metaanalyse kann diese Empfehlung auch auf Frauen mit Abortus-imminens-Blutung und 1 oder 2 spontanen Fehlgeburten in der Anamnese ausgeweitet werden 124 .…”
Section: Leitlinieunclassified